1996
DOI: 10.1002/(sici)1096-9861(19961104)375:1<1::aid-cne1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of AMPA receptors and glutamate during pre- and postnatal development in the visual cortex of ferrets

Abstract: Immunohistochemical methods were used to study the distribution and time-course of appearance of cells expressing glutamate and alpha-amino-3-hydroxy-5-methyl-4-isoaxazole propionic acid (AMPA)-type glutamate receptors (GluR1 and GluR2/3) during development of the ferret visual cortex. Glutamate is present in many neurons in the ventricular zone, intermediate zone, developing cortical plate, and marginal zone as early as embryonic day (E) 34 (birth is at E41 in ferrets). Glutamate attains its adult distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 94 publications
0
8
1
Order By: Relevance
“…Thus, during corticogenesis at late embryonic and early postnatal periods, glutamate transport by neurons, specifically via EAAC1, may predominate over astroglial transport of glutamate. Expression of EAAC1 at high levels in the external plexiform layer appears to coincide with the maturation of the apical dendritic bouquets of pyramidal neurons (MarĂ­n-Padilla, 1992) at a time when non-NMDA glutamate receptors are also highly enriched in the marginal zone (Furuta et al, 1995;Herrmann, 1996;Martin et al, 1997b). Glutamatergic mechanisms are operative in undifferentiated proliferative zones during embryogenesis.…”
Section: Glutamate Transporter Expression During Morphogenesismentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, during corticogenesis at late embryonic and early postnatal periods, glutamate transport by neurons, specifically via EAAC1, may predominate over astroglial transport of glutamate. Expression of EAAC1 at high levels in the external plexiform layer appears to coincide with the maturation of the apical dendritic bouquets of pyramidal neurons (MarĂ­n-Padilla, 1992) at a time when non-NMDA glutamate receptors are also highly enriched in the marginal zone (Furuta et al, 1995;Herrmann, 1996;Martin et al, 1997b). Glutamatergic mechanisms are operative in undifferentiated proliferative zones during embryogenesis.…”
Section: Glutamate Transporter Expression During Morphogenesismentioning
confidence: 95%
“…Glutamatergic mechanisms are operative in undifferentiated proliferative zones during embryogenesis. Glutamate activates non-NMDA glutamate receptors in the ventricular zone (LoTurco et al, 1995), and AM PA receptor protein is expressed in proliferative zones in developing ferret (Herrmann, 1996), rat (Martin et al, 1997b), and ovine brain (Furuta et al, 1995). GL AST and GLT-1 mRNAs are expressed in the ventricular zone of embryonic mouse brain Sutherland et al, 1996); although, at low levels, we found GL AST immunoreactivity in the ventricular and subventricular zones of the telencephalon and GLT-l and EAAC1 immunoreactivities in the ganglionic eminence.…”
Section: Glutamate Transporter Expression During Morphogenesismentioning
confidence: 99%
“…N -Methyl- d -aspartate (NMDA), α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) and kainate receptors and the essential subunits for their receptor function have been demonstrated in the subplate of various species, suggesting the presence of functional glutamatergic synapses in subplate neurons (Herrmann, 1996; Aoki, 1997; Catalano et al, 1997; Furuta and Martin, 1999). The expression of benzodiazepine binding sites (Schlumpf et al, 1983), GABA A receptors (Huntley et al, 1990) and GABA A receptor subunits (Meinecke and Rakic, 1992) in the subplate indicate that functional GABAergic synaptic inputs should also be present in subplate neurons.…”
Section: Structural Properties Of Subplate Neuronsmentioning
confidence: 99%
“…In adult brain there is generally a correlation between glutamate uptake and glutamatergic ac- tivity in different brain regions (Kugler, 1993). Indeed, a-amino-3-hydroxy-5-methyli soxazole-4-propionate (AMPA) receptor protein is expressed in proliferative zones in developing ferret (Herrmann, 1996) and in rat (A. Furuta, personal observation).…”
Section: Role Of Eaat1 In the Proliferative Periventricular Zone Durimentioning
confidence: 99%